2009
DOI: 10.1016/j.ejcts.2008.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Extracardiac approaches to protecting the heart☆

Abstract: Myocardial adaptation to ischemia in the form of ischemic preconditioning is clinically attractive, but not easily usable in cardiac surgery until molecular mimics are discovered. The various forms of pre- and postconditioning, including remote preconditioning, indicate that a 'universal' protection is evoked. A growing body of evidence indicates that events underlying myocardial adaptation to ischemia may either involve, or be parallel to, signaling of the innate immune response. The heart can be protected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…Ischemic conditioning is an endogenous way to protect the heart from ischemia‐reperfusion injury using repetitive brief episodes of ischemia, evoking myocardial protection when applied either locally or distantly . Expanding upon the principle of remote therapy to protect the heart, gene therapy through delivery of DNA to peripheral organs has been performed successfully.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic conditioning is an endogenous way to protect the heart from ischemia‐reperfusion injury using repetitive brief episodes of ischemia, evoking myocardial protection when applied either locally or distantly . Expanding upon the principle of remote therapy to protect the heart, gene therapy through delivery of DNA to peripheral organs has been performed successfully.…”
Section: Introductionmentioning
confidence: 99%
“…However, efficient and safe gene delivery to targeted cells in the heart in vivo is still an unresolved enigma. Genes can be injected to the heart directly into the myocardium, delivered through the coronary arteries or veins, or into the pericardium (Valen, 2009). Of those options a direct myocardial injection is the approach most likely to succeed (Valen, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Genes can be injected to the heart directly into the myocardium, delivered through the coronary arteries or veins, or into the pericardium (Valen, 2009). Of those options a direct myocardial injection is the approach most likely to succeed (Valen, 2009). However, this is an invasive procedure due to the hearts' protective placement in the thorax and is thus unlikely to represent a large-scale clinical treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Early studies involving the anti-C5 complement agent did demonstrate a mortality benefit (1.8% vs 5.9%, p=0.01)26 27; however, the subsequent APEX MI trial found no differences in mortality or composite end points 28. Increased knowledge of cytokine and chemokine pathways in the reperfusion response may identify novel modifiable targets for innovative therapeutic agents aimed at amplifying the benefits of reperfusion therapy 29 30…”
Section: Adequacy Of Reperfusionmentioning
confidence: 99%